HEREDITARY SPASTIC PARAPLEGIA: DIAGNOSTIC AND TREATMENT FEATURES (Herald of the National Children's Medical Center, 2025)
Hereditary spastic paraplegia (HSP) is a group of rare genetic neurological disorders characterized by progressive damage to the long motor tracts (pyramidal system), leading to chronic spasticity and weakness in the lower limbs. Despite its slowly progressive nature, the disease significantly reduces the quality of life in children and requires a comprehensive approach to diagnosis and treatment.
Keywords: hereditary spastic paraplegia; children; diagnosis; botulinum therapy; spasticity; rehabilitation